Evaluating the epidemiology of vaginitis in a contemporary cohort: a population-based study - Church, Deirdre; Naugler, Christopher; Guo, Maggie; Somayaji, Ranjani (Frontiers in Public Health, 2025)
IntroductionBacterial vaginosis (BV), vulvovaginal candidiasis (VVC), and Trichomonas vaginalis (TV) commonly cause infectious vaginitis in women, especially those of reproductive age. Characterization of the epidemiology of infectious vaginitis in a contemporary population-based cohort was done to determine the longitudinal age-standardized and sex-based testing, positivity, and incidence rates and ratios of infectious vaginitis in a large Canadian healthcare region.MethodsWe conducted a population-based cohort study from March 2015 through March 2018 using the Alberta Precision Laboratories (APL) microbiology database. Calgary 2016 census data was used to calculate incidence rates (IR) and ratios (IRR) for cases and testing rates.ResultsFor testing and positivity, female sex, and younger age groups were associated with increased risk of BV, VVC, and TV infections. The annual mean population in 2016 was 1,411,660 individuals (50.3% female). A total of 40,259 cases/293,853 tests (13.7%) of BV, 32,894 cases/293,853 tests (11.2%) of VVC, and 2018 cases/342,986 tests (0.7%) of TV were identified. The overall IR for BV ranged from 0 to 609 cases per 10,000 person-years. The overall IR for VVC ranged from 0 to 445 per 10,000 person-years. The overall IR for TV ranged from 0 to 27 per 10,000 person-years. The highest age-specific testing positivity rate and IR rate for BV and VVC occurred in women aged 20–34 years and 20–34 years. For TV, female IR for BV, VVC, and TV remained stable during the study.DiscussionThese unique regional data provide insight for the development of appropriate age-specific clinical testing criteria according to relative risk of acquisition of each vaginitis agent.